Amino, ammonio and aminioethenes: a theoretical study of their structure and energetics. (28th May 2013) - Miranda, Margarida S.; Esteves da Silva, Joaquim C. G.; Castillo, Alvaro; Frank, Aaron T.; Greer, Alexander; Brown, Jodian A.; Davis, Brittny C.; Liebman, Joel F.
<x xml:space="preserve">Abstract</x> We have performed high level ab initio quantum mechanical calculations for aminoethene and the three isomeric 1, 1‐ (Z)‐ or (E)‐1, 2‐diaminoethenes as well as their singly and doubly charged cations derived by loss of electrons and/or upon protonation. Gas phase molecular structures were computed at the MP2/6‐311 + G(3df, 2p) level. Standard molar enthalpies of formation in the gas phase, at T = 298.15 K, were estimated using the G3 composite method and atomization, isodesmic and homodesmotic reactions. Other energetic parameters were also calculated at the G3 level: proton affinities, basicities and adiabatic ionization enthalpies. Theoretical and experimental data are compared. The reported experimental data refer only to aminoethene wherein the standard molar enthalpy of formation has a considerable uncertainty, although the molecular structure is well established. There are no such data, neither structural nor thermochemical, for any of the three isomeric diaminoethenes. Isoelectronic comparisons are made. For example, the diprotonated diaminoethenes are isoelectronic to isobutene and (Z)‐ and (E)‐butene, while the doubly ionized diaminoethenes are likewise related to trimethylenemethane and 1, 3‐butadiene. Copyright © 2013 John Wiley & Sons, Ltd.